A Utilization Of Ulva Lactuca As An Alternative Increase Iron Youth - Ghassani, Putri Marini (Politeknik NEST, 2025)
The incidence of anemia in adolescent girls in Indonesia is still relatively high. Anemia can occur because young women experience menstruation every month. This can reduce the quality of health and life. One of the efforts to increase the consumption of iron sources can be done by processing interesting foods with the use of local food ingredients. Seaweed is a biological plant that is widely found in Indonesian waters, one of which is ulva lactuca seaweed. This seaweed is found on the beach along Kukup, Yogyakarta. Utilization of seaweed type ulva lactuca can be used as a side dish, namely grilled rice with additional processed tuna fish. This study aims to analyze the nutritional content in the form of proximate and iron tests as well as organoleptic tests on roasted rice, seaweed, ulva lactuca and processed tuna. This research method uses research and development methods (Research and Development) with a 4D model. This research consists of the process of making roasted rice using black rice, ulva lactuca seaweed, processed tuna and broccoli. The results of the analysis of the content of water, ash, fat, protein, carbohydrates, crude fiber and calories per 100 g were 61.50, 1.66, 7.03, 9.87, 20.03, 0.31% and 170 respectively kcal, while the iron content is 49%. This grilled rice can be accepted by the panelists with a score of 4.8 on the overall trait. In conclusion, ulva lactuca seaweed and processed tuna can be used in the manufacture of baked rice which contains seaweed in it.